(3GdeTjNI GdHGSeI ddbHGHi haGWeIs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3GHf MLQ GdYSbdGfj,J (B852 (3g` s ((3eMeO Hf eMeO Hf CHj TQja GdebOSi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI s
(3BNQgG (B:s
(3BNQ GdeTjNI GdHGSeI ddbHGHi s
(3NQL ajgG CSeGA TjhN Jbi GdOjf YHOGdQMef Hf YeQ GdbHGHi Ke GdebOSi GdMfHdis
(3JHUQI GdYfhGf (B:s
(3JNQjLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B69 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B276 s
Keywords: (3GdJGQjNs